Surfing Tour Package Planning in Pesisir Barat Area of Lampung - Adi Hendraningrum; Anda Prasetyo Ery; Deddy Adisudharma; Muhammad Janwarls Qadri; Dede Kuswandi (Politeknik Pariwisata Makassar, 2024)
In Pesisir Barat Regency, Lampung Province, marine tourism, particularly surfing, shows significant potential for development. Tanjung Setia Beach stands out as a major surfing destination due to its high and long waves. The successful organization of the World Surf League (WSL) Krui Pro 2022 in this area has increased its global appeal and attracted the interest of PT. Fres Indonesia Wisata as a travel agency. This prompted a study to explore surf tour package planning in Pesisir Barat Regency. The results showed that the preferred tourist attractions for surf packages include Tanjung Setia Beach, Mandiri Beach, Labuhan Jukung Beach, Melasti Beach, Pisang Island, and Batu Tihang. The region offers extensive accommodation, dining, transportation, entertainment and shopping facilities mostly located in the city area. Most of the tourists who come to surf are from Australia with a duration of stay ranging from five days to one month. Based on the findings, PT. Fres Indonesia Wisata is advised to consider three recommended tour packages: Krui Fun Surf For Beginner (5D4N), The Charm Of Krui (5D4N), and Exotic Krui Surf (7D6N). These packages correspond to identified needs and preferences, which have the potential to increase the attractiveness of the region as a surfing destination. This research used a descriptive qualitative approach with data collection methods in the form of documentation, interviews, and observation. Data analysis was conducted through reduction, presentation, and conclusion drawing, with data validity secured through source triangulation. The study identified four important dimensions in the development of tour packages: Tourist Attractions, Travelers, Facilities, and Time